Design and the Function of Branding as a Marker of a Religious and Creative City: Martapura the City of Diamond, Serambi of Mecca, and Santri - Saputra, Riza (Proceeding International Conference on Religion, Science and Education, 2022)
This research aims to identify a branding city to indicate a creative and religious city, particularly in Martapura City, South Borneo. Utilizing three brandings: Diamond, Serambi Mecca, and santri has a fundamental value to attract tourists. Moreover, these three brandings encourage the local government to re-create a precise design of the city. The function of Branding generally aims to attract tourists, but it also has many functions, such as a designation of the city's construction and pride of society within. The image of the city and the behavior of communities are in line with the brandings of the city. This study has used literature research and surveying information to the conduct of society in adjustment with an installation of city's Branding as the local community's pride.